2019
DOI: 10.21580/jiafr.2019.1.1.3733
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tax planning, company value, and leverage on income smoothing practices in companies listed on Jakarta Islamic Index

Abstract: <p><strong>Purpose</strong> - The purpose of this paper is to identify the effect of tax planning, company value, and leverage on income smoothing practice in companies listed on the Jakarta Islamic Index for the period 2010-2017.</p><p><strong>Method</strong> - The data in this study consisted of 12 companies listed on the Jakarta Islamic Index for the period 2010-2017. Samples are selected using the purposive sampling method. Eckel Index classification uses two types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 2 publications
2
8
0
1
Order By: Relevance
“…However, companies have not made optimal use of financial reporting via the Internet, such as insufficient website facilities and the content component/content that only contains an annual report even though other items are also important to be informed. These research results are in line with the research of Novitasari (2017) and Megarani, Warno & Fauzi (2019) but contrast with the research of Meirawati et al (2018).…”
Section: The Effect Of Internet Financial Reporting On Firm Valuesupporting
confidence: 83%
“…However, companies have not made optimal use of financial reporting via the Internet, such as insufficient website facilities and the content component/content that only contains an annual report even though other items are also important to be informed. These research results are in line with the research of Novitasari (2017) and Megarani, Warno & Fauzi (2019) but contrast with the research of Meirawati et al (2018).…”
Section: The Effect Of Internet Financial Reporting On Firm Valuesupporting
confidence: 83%
“…Tax aggressiveness is usually referred to as an action taken by management with the aim of minimizing the taxable profit of the company obtained through tax planning, whether legally or illegally (Megarani et al, 2019). Tax-aggressive companies are characterized by less transparency.…”
Section: Tax Aggressivenessmentioning
confidence: 99%
“…Therefore, the agency theory, revealed that management has more information about the company. Indirectly, a manager has a broad opportunity to take action to obtain accounting decisions corresponding necessity the company (Megarani, Warno, & Fauzi, 2019). Accounting can be seen as an art, science, or technology.…”
Section: Financial Statements Definitionmentioning
confidence: 99%